Kinetics of Ep stage in kraft pulp ECF bleaching - Mendez, Claudia Marcela (2009)
The purpose of bleaching is to eliminate the groups responsible for pulp colour. These chromophoric groups are eliminated or transformed by means of chemical reactions. In alkaline stages reinforced with hydrogen peroxide, chromophoric groups react with perhydroxyl anion (HOO-).This work has studied the kinetics of Ep stage in a pine kraft pulp bleaching plant with bleaching sequence DE0D1 EpD2 , using for this purpose industrial samples collected at the end of D1 stage. Ep stage bleaching simulation was laboratory conducted at temperatures ranging from 68.3ºC to 93.7ºC, initial concentrations of H2 O2 between 0.11% on o.d. (ovendry) pulp and 0.39% on o.d. pulp, and NaOH% on o.d. pulp / H2O2 % on o.d. pulp ratio equal to 3, in order to maintain alkalinity. 0.025% on o.d. pulp of DTPMPA was applied to all samples as chelant, to avoid hydrogen peroxide decomposition reactions, catalysed by the presence of metal ions. In the bleaching liquors, pH and consumed hydrogen peroxide were measured after 5, 10, 20, 45, 90, 180, and 240 minutes’ reaction, as well as brightness values and the coefficients of light absorption of the pulps.The results indicate that kinetics is complex, and two stages are observed as a minimum in the Ep stage of the bleaching process (the first one faster than the second one). As far as chromophor concentration is concerned, the first stage can be considered as a first order reaction. For a given initial concentration of hydrogen peroxide (0.15% on o.d. pulp and 0.25% on o.d. pulp), the value of the velocity constant increases as a function of temperature. The concurrent reactions (hydrogen peroxide decomposition) become more important at higher temperatures.